Authorization to make expenses - definition problems in the field of liability for breach of public finance discipline (Discourse of Law and Administration, 2022)
One of the basic violations subject to liability for violating public finance discipline is expenditure from public funds without authorization or with exceeding the authorization specified in the relevant acts of financial planning. The act on liability for violating public finance discipline does not, however, define the terms used by the legislator in penalizing acts. In this regard, it refers to terms in the meaning given by the Public Finance Act. Such a legislative procedure with regard to the scope of the reference as well as difficulties resulting from the possibility of determining the meaning of these terms in the Public Finance Act causes certain effects in the form of limiting the effectiveness of sanctioning norms and the consequences of non-liability for violations in this area.
Keywords: public expenditure; public finances; responsibility for violating public finance discipline; financial plan